Upaya Perencanaan Komunikasi Humas Dinas Sosial Kota Tangerang dalam Pelayanan Publik pada Penanganan Orang Terlantar: Pengemis Gelandangan - Agustiana, Elyza Zahra; Mirza, Mochammad; Delima, Isniyunisyafna Diah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Neglected people and beggars are one of the important social welfare problems (PMKS) that need to be addressed because the number of abandoned people and homeless beggars in Tangerang City is quite large and continues to increase and really needs support and assistance from the government. The Tangerang City Social Service plays a role in meeting needs related to physical, psychological, social and economic aspects. The theoretical model used in this research is the Culip and Center communication planning theoretical model which has 4 stages, namely; Fact Finding, Planning and Programming, Taking Action and Communicating, Evaluating. The results of this research explain that the Tangerang City Social Service has 4 efforts to improve public services in taking care of neglected communities (beggars), namely: 1. Facilities in the form of accommodation for people who need social services, education or socialization efforts related to health problems, 2. Increasing awareness, motivation to become individuals who are more independent, efficient and socialize effectively, 3. Advocacy efforts by providing skills training according to their interests, aiming to increase productivity. 4. Technical efforts to meet the needs of refugees in terms of data collection.